Publisher Correction: Quantitative and organisational changes in mature extracellular matrix revealed through high-content imaging of total protein fluorescently stained in situ. Issue 1 (December 2017) - Holdsworth, Gill; Bon, Hélène; Bergin, Marianne; Qureshi, Omar; Paveley, Ross; Atkinson, John; Huang, Linghong; Tewari, Roohi; Twomey, Breda; Johnson, Timothy
A correction to this article has been published and is linked from the HTML version of this paper. The error has been fixed in the paper.